Microbe Mediated Extraction of Keratin from Gallus gallus domesticus and its Role as a Fertilizer and in Poultry Feed - Sahar Noor; Aisha Waheed Qurashi; Roheela Yasmeen (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The poultry industry in Pakistan generates substantial feather waste, contributing to environmental contamination. This study aimed to isolate keratinolytic bacteria from chicken (Gallus gallus domesticus) feathers and soil samples. Twelve isolates exhibited proteolytic activity, forming clear zones on skim milk agar and growing efficiently on minimal agar, suggesting they belong to the Bacillus species. One promising strain, identified through 16S rRNA sequencing as Pseudomonas aeruginosa, demonstrated optimal feather degradation at pH 7.0-9.0 and temperatures of 37 °C and 45 °C. Protein content was measured as 4.8 mg/ml for chicken feathers and 5.43 mg/ml for quail feathers (p < 0.05). The FTIR spectrum of keratin hydrolysate for the chicken feathers was recorded within 4000-7000 cm⁻¹. Strain SC7 showed significant plant microbial interaction with tomato (Solanum lycopersicum), pea (Pisum sativum), and cucumber (Cucumis sativus), with dilutions of 100x (0.048 mg/ml) and 70x (0.068 mg/ml) promoting the growth of tomato, pea, and cucumber. When used as a feed additive, keratin significantly (p < 0.05) increased chicken body weight by 67.7% compared to controls. Liver function tests (ALT, AST, ALP, total protein, albumin, globulin, albumin/globulin ratio) showed decreased ALT and AST and increased ALP, total protein, albumin, and globulin in the experimental group compared to controls. Histopathology revealed no degenerative effects of keratin on chicken liver hepatocytes.